Pengaruh Penggunaan Media YouTube terhadap Kemampuan Menceritakan Kembali Isi Iklan pada Peserta Didik Kelas VIII SMP Negeri 1 Karangawen Tahun Pelajaran 2023/2024 - Dyah Wiyati Kusumaningtyas; Ngatmini Ngatmini; Siti Ulfiyani (CV. Alim's Publishing, 2024)
This research aims to determine the effect of using YouTube media on the ability to retell advertising content in class VIII students at SMP Negeri 1 Karangawen for the 2023/2024 academic year. The type of research used is true experimental with a Posttest Only Control Design. The population of this study was all students in class VIII of SMP Negeri 1 Karangawen and the selected samples were class VIII B as the control class and class VIII C as the experimental class. The data collection technique uses a test technique in the form of a posttest retelling the contents of the advertisement. Data analysis techniques used include validity testing, reliability testing, normality testing, homogeneity testing and hypothesis testing. The results of the hypothesis test showed that there was a difference between the experimental and control class posttests. The results obtained were tcount 0.391 > ttable 0.254 and significance 0.00 < 0.05. Based on these results, it can be concluded that there is an influence of the use of YouTube media on the ability to retell the content of advertisements in class VIII students at SMP Negeri 1 Karangawen for the 2023/2024 academic year.